1998
DOI: 10.1029/98jd02852
|View full text |Cite
|
Sign up to set email alerts
|

Broadband lidar measurements of tropospheric water vapor profiles

Abstract: Abstract. A new technique has been developed for the measurement of vertical profiles of water vapor in the troposphere. The method, which is also appropriate for the measurement of gases such as ozone and nitrogen dioxide, is based on the application of differential optical absorption spectroscopy (DOAS) to backscattered photons from a broadband lidar (10-20 nm at full width half maximum) operating in the UV-visible region of the electromagnetic spectrum. ANd: YAG pumped broadband dye laser is used as the lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The derivation of Equation 1 can be found in Newsom et al (2020). While Vaisala's water-vapour retrieval algorithm is proprietary, it is similar to the broad-band water-vapour DIAL solution presented in South et al (1998). Solving for the water-vapour transmission profile provides the number-density profile for water vapour via the Beer-Lambert law.…”
Section: Vaisala Dialmentioning
confidence: 99%
See 1 more Smart Citation
“…The derivation of Equation 1 can be found in Newsom et al (2020). While Vaisala's water-vapour retrieval algorithm is proprietary, it is similar to the broad-band water-vapour DIAL solution presented in South et al (1998). Solving for the water-vapour transmission profile provides the number-density profile for water vapour via the Beer-Lambert law.…”
Section: Vaisala Dialmentioning
confidence: 99%
“…Both techniques have their advantages and disadvantages, but for the purposes of this study we will focus on the DIAL technique. The DIAL technique has been applied to water‐vapour measurements since the early 1990s for both ground‐ and air‐based lidars (South et al ., 1998; Wulfmeyer and Bösenberg, 1998; Wagner and Pruß, 2002; Spuler et al ., 2015). Water‐vapour DIALs are now starting to be developed for automated and operational use (Spuler et al ., 2015; Newsom et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While a number of nighttime studies at ground level close to local sources of NO have observed a limited role of NO 3 in nighttime radical production owing to surface losses of NO 3 and the rapid reaction between NO 3 and NO (Salisbury et al, 2001;Fleming et al, 2006;Sommariva et al, 2007;Kanaya et al, 1999Kanaya et al, , 2002Kanaya et al, , 2007aEmmerson and Carslaw, 2009;Faloona et al, 2001;Martinez et al, 2003;Ren et al, 2003Ren et al, , 2005Ren et al, , 2006Volkamer et al, 2010), several studies of NO 3 and N 2 O 5 above ground level and in more remote regions have indicated a more significant role for NO 3 in nighttime radical production and tropospheric oxidation (Platt et al, 1980;Povey et al, 1998;South et al, 1998;Aliwell et al, 1998;Allan et al, 2002;Stutz et al, 2004;Brown et al, 2003Brown et al, , 2004Brown et al, , 2007Brown et al, , 2009Brown et al, , 2011Aldener et al, 2006;Sommariva et al, 2009;Stutz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of NO 3 have been overestimated by model calculations in several studies (Mihelcic et al, 1993;Sommariva et al, , 2007, with those of nighttime OH and HO 2 radicals typically underestimated, indicating poor understanding of nighttime tropospheric oxidation processes (Kanaya et al, 1999(Kanaya et al, , 2002(Kanaya et al, , 2007aEmmerson and Carslaw, 2009;Geyer et al, 2003;Faloona et al, 2001;Martinez et al, 2003;Ren et al, 2006). While a number of nighttime studies at ground level close to local sources of NO have observed a limited role of NO 3 in nighttime radical production owing to surface losses of NO 3 and the rapid reaction between NO 3 and NO (Salisbury et al, 2001;Fleming et al, 2006;Sommariva et al, 2007;Kanaya et al, 1999Kanaya et al, , 2002Kanaya et al, , 2007aEmmerson and Carslaw, 2009;Faloona et al, 2001;Martinez et al, 2003;Ren et al, 2003Ren et al, , 2005Ren et al, , 2006Volkamer et al, 2010), several studies of NO 3 and N 2 O 5 above ground level and in more remote regions have indicated a more significant role for NO 3 in nighttime radical production and tropospheric oxidation (Platt et al, 1980;Povey et al, 1998;South et al, 1998;Aliwell et al, 1998;Allan et al, 2002;Stutz et al, 2004;Brown et al, 2003Brown et al, , 2004Brown et al, , 2006Brown et al, , 2007Brown et al, , 2009...…”
Section: Introductionmentioning
confidence: 99%